Absolute first trimester cell‐free DNA levels and their associations with adverse pregnancy outcomes. (10th November 2016) - Thurik, Florentine F.; Lamain‐de Ruiter, Marije; Javadi, Ahmad; Kwee, Anneke; Woortmeijer, Heleen; Page‐Christiaens, Godelieve C. M. L.; Franx, Arie; van der Schoot, C. Ellen; Koster, Maria P. H.
Abstract: Objective: To study associations of first trimester cell‐free fetal DNA levels (in this paper referred to as cell‐free placental DNA (cfpDNA) levels) and preeclampsia (PE), pregnancy‐induced hypertension (PIH), gestational diabetes (GDM) and spontaneous preterm birth (sPB). Method: A nested case‐control study was conducted in first trimester samples (gestational age 8 +0 −13 +6  weeks). A total of 226 cases and 301 controls were included. CfpDNA levels were quantified in male‐bearing pregnancies using real‐time DYS14‐PCRs on DNA isolated from maternal serum. CfpDNA multiples of the median (MoMs) were calculated based on associations with patient characteristics (body mass index, parity, ethnicity and smoking). Associations between MoMs and adverse outcomes were studied. Results: Cell‐free placental DNA levels were negatively associated with body mass index (β = −0.297, p  < 0.001) and smoking (β = −0.163, p  = 0.006). MoMs were lower in women who later developed PIH ( n  = 84, p  = 0.009) or GDM ( n  = 56, p  = 0.037). There was no association between cfpDNA MoMs and PE ( n  = 37, p  = 0.15) or sPB ( n  = 49, p  = 0.19). CfpDNA was positively correlated with pregnancy‐associated plasma protein A ( r  = 0.426, p  < 0.001) but not with placental growth factor ( r  = 0.059, p  = 0.179). Conclusion: Adjusted first trimester cfpDNA levels are associated with PIH and GDM but probably not with PE or sPB. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? First trimester cell‐free placental DNA (cfpDNA) levels in maternal blood, measured in mid or late pregnancy, are associated with several adverse pregnancy outcomes, such as preeclampsia and preterm birth. What does this study adds? There is no association of first trimester cfpDNA levels with preeclampsia and spontaneous preterm birth. First trimester cfpDNA levels are associated with pregnancy‐induced hypertension and gestational diabetes mellitus. First trimester cfpDNA levels are correlated with PAPP‐A but probably not with PlGF.